2016
DOI: 10.1590/2317-1782/20162015143
|View full text |Cite
|
Sign up to set email alerts
|

Educação mediada por tecnologia em Fonoaudiologia: impacto na motivação para aprendizagem sobre o Sistema Miofuncional Orofacial

Abstract: RESUMO O objetivo deste estudo foi comparar três métodos de aprendizagem sobre Anatomia e Fisiologia do Sistema Miofuncional Orofacial quanto à motivação para a aprendizagem em Fonoaudiologia. Participaram 36 estudantes do segundo ano de graduação, após assinatura de termo de consentimento livre e esclarecido. Cada estudante foi alocado randomicamente nos grupos: Grupo I (GI) – 12 participantes do Método Interativo 1 (MI1); Grupo II (GII) – 12 participantes do Método Interativo 2 (MI2); Grupo III (GIII) – 12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Teaching and learning methods that contemplate the use of computer games and computational models need to be expanded, better controlled, and improved, especially in relation to the methods of assessing student knowledge retention (9,23) and the transfer of knowledge to clinical practice situations (29) . This study brings an initiative to improve knowledge related to conceptual learning, through interactive methods in SLHS teaching, considering that there is still little research in the area addressing this theme (11,12,18,30) . Further studies addressing other aspects that interfere with computer-assisted instruction (CAI), such as cognitive effort and time exposure to proposed educational methods, need to be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teaching and learning methods that contemplate the use of computer games and computational models need to be expanded, better controlled, and improved, especially in relation to the methods of assessing student knowledge retention (9,23) and the transfer of knowledge to clinical practice situations (29) . This study brings an initiative to improve knowledge related to conceptual learning, through interactive methods in SLHS teaching, considering that there is still little research in the area addressing this theme (11,12,18,30) . Further studies addressing other aspects that interfere with computer-assisted instruction (CAI), such as cognitive effort and time exposure to proposed educational methods, need to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In Speech-Language and Hearing Sciences (SLHS), a previous study showed that the use of a computer game as a tool complementary to the teaching and learning process was as efficient as the traditional method of teaching regarding the short-term conceptual knowledge retention of students, and that the traditional method was more efficient for long-term knowledge retention (11) . A second study conducted by the same research group identified positive results regarding learning motivation, with better results for the use of a 3D computational model, followed by a 2D computer game, compared with the traditional learning method (12) .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation